Investigating Misogynistic Themes in Modern Dramas: A Case Study of Pakistani Drama Noor Jahan: - Rimsha Akram (Journal of English Language Teaching and Applied Linguistics, 2025)
Background of the Study: Television dramas significantly shape public perception, particularly in gender-related issues. In South Asian contexts, media often promotes patriarchal values by repeatedly portraying women in submissive and marginalized roles. Aims and Scope of the Paper: This study investigates the misogynistic themes embedded in the modern Pakistani television drama Noor Jahan. It focuses not only on male dominance but also explores matriarchal misogyny, where women themselves contribute to the oppression of other women. Methods: Adopting a qualitative research approach, this study applies Sara Mills’ Feminist Stylistics (1995) to analyze selected episodes of Noor Jahan. Through thematic and linguistic analysis of dialogues, the study identifies power imbalances and gender bias reinforced through language. Results: Findings reveal that misogyny is perpetuated not only by male characters but also by female ones, especially the antagonist, Noor Jahan. Women are portrayed as limited to domestic roles and often shown as burdens or sources of dishonor. Linguistic choices such as “kam zaat aurat” and “main ek kaneez hoon” reflect deep-rooted gender discrimination. Conclusion: Media, especially television, plays a critical role in reinforcing or challenging societal norms. The drama Noor Jahan reinforces negative gender roles, which may influence youth perceptions. There is a pressing need for media to shift its narrative highlighting women’s strength, independence, and diverse roles in society.